Testicular torsion: sonomorphological appearance as a predictor for testicular viability and outcome in neonates and children - Chmelnik, Martin; Schenk, Jens-Peter; Hinz, Ulf; Holland-Cunz, Stefan; Günther, Patrick (Pediatric surgery international, 2010)
INTRODUCTION: Testicular torsion in children is found both in neonates [perinatal testicular torsion (PTT), <30th day of life] and in older children [testicular torsion (TT)]. Prediction of testicular viability is essential for deciding whether to perform emergency exploration surgery. The aim of the present study, therefore, was to investigate the sonomorphological parameters as predictors for testicular viability. - MATERIALS AND METHODS: All our cases of sonographically diagnosed and surgically confirmed testicular torsion (n = 25) in a 7.5-year period were reviewed. We evaluated the overall group and two subgroups, PTT (n = 9) and TT (n = 16), and assessed the following sonomorphological parameters: normal echogenicity (homogeneous), diffuse hyper-/hypoechogenicity (homogeneous) and focal hyper-/hypoechogenicity (heterogeneous). These findings were correlated with the testicular recovery rate. - RESULTS: In both groups, we found the highest recovery rates in testes with normal, homogeneous echogenicity and a zero recovery rate in testes with heterogeneous echogenicity (p = 0.0117). - CONCLUSIONS: By using the sonomorpohological criteria presented here, testicular viability can be appraised in all age groups to help determine the prognosis for testicular outcome. In PTT, a nonperfused, homogeneously appearing testis represents the initial phase of torsion. Only for this type is there hope for salvage. In addition to the intraoperative appearance, a testis that is preoperatively heterogeneous in appearance can support the decision for orchiectomy.
Published online: 18 November 2009
Gesehen am 13.03.2023